CHARACTERIZATION OF TWO CANNONBALLS FROM THE ROYAL AMMUNITION FACTORY OF EUGI - Zalakain, Iñaki; Berlanga, Carlos; Álvarez, Lucas; Asa, Luis E; Labé, Paco; Rivero, Pedro J; Valencia, Javier; Rodríguez, Rafael (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
In this report, several materials including two different cannonballs, calcined ore and slags from The Royal Ammunition Factory of Eugi in Navarra (Spain) have been analysed. Both cannonballs presented a spherical shape with an excellent degree of conservation, belonging to last years of the factory production (1766-1850). Several techniques such as microhardness, X-ray fluorescence, optical and scanning electron microscopy, and EDX analysis were used in order to identify the employed manufacture in the elaboration process. The results showed a great difference in their chemical composition, mainly related to the silicon and phosphorous concentration. One of them exhibited an unusual amount of phosphorous, being probably due to the employed ore. In addition, the metallographic characterization revealed that one of them was composed by a ledeburitic matrix with graphite and steadite, whereas the second one exhibited a ferritic-pearlitic matrix with a significant amount of steadite. Consequently, their mechanical properties varied and as result, the choice about the type of cannonball would depend on the final utilization as a round shot or grapeshot.